2016
DOI: 10.1158/1078-0432.ccr-16-0224
|View full text |Cite
|
Sign up to set email alerts
|

Dual Faces of IFNγ in Cancer Progression: A Role of PD-L1 Induction in the Determination of Pro- and Antitumor Immunity

Abstract: IFNg is a cytokine that plays a pivotal role in antitumor host immunity. IFNg elicits potent antitumor immunity by inducing Th1 polarization, CTL activation, and dendritic cell tumoricidal activity. However, there are significant discrepancies in our understanding of the role of IFNg as an antitumor cytokine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
284
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(302 citation statements)
references
References 47 publications
16
284
0
2
Order By: Relevance
“…29,30 In addition, since blood endothelial cells express PD-L1, 31 CAS cells may express PD-L1 intrinsically. In vitro experiments using CAS cell lines exhibited PD-L1 expression in cancer cells irrespective of IFNg stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In addition, since blood endothelial cells express PD-L1, 31 CAS cells may express PD-L1 intrinsically. In vitro experiments using CAS cell lines exhibited PD-L1 expression in cancer cells irrespective of IFNg stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, PD-L1 is involved in dual aspects of immuno-suppression and immuno-stimulation dependent on the current condition. The well-known mechanism for immuno-stimulation is through IFN-γ productions by effector T cells such as tumor-infiltrating lymphocytes (TILs), which, in turn, upregulate PD-L1 expression on tumor cells (13). Interestingly, there were also upregulated genes in the PD-L1-negative group compared with the PD-L1-positive group: B7H3 and B7H4.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 We next sought to determine whether IFNg also regulates PD-L1 expression in MDSCs. We first analyzed IFNg expression level in the tumor microenvironment.…”
Section: Pd-l1 Expression In Mdscs Depends On Mdsc Anatomic Locationsmentioning
confidence: 99%
“…6,[16][17][18][19][20] It has been shown that PD-L1 is constitutively expressed in various types of tumor cells and regulated by oncogenes. [18][19][20] Furthermore, PD-L1 expression can be upregulated by inflammatory cytokines such as IFNg [20][21][22][23] In addition to expression in tumor cells, PD-L1 is also expressed on subsets of T cells, NK cells, macrophages, myeloid DCs, B cells, epithelial cells and vascular endothelial cells. [24][25][26][27] PD-L1 is notably expressed on mature macrophages, particularly in activated macrophages.…”
Section: Introductionmentioning
confidence: 99%